If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x-36x+6=8x-12
We move all terms to the left:
6x-36x+6-(8x-12)=0
We add all the numbers together, and all the variables
-30x-(8x-12)+6=0
We get rid of parentheses
-30x-8x+12+6=0
We add all the numbers together, and all the variables
-38x+18=0
We move all terms containing x to the left, all other terms to the right
-38x=-18
x=-18/-38
x=9/19
| x÷4=x-12 | | F(a)=2a^2-a+2 | | 9(x-8)-2=-74 | | 1/6y=-15 | | x+7.9=9.8 | | 49.10=x+5 | | 6a+9=45 | | 5a−5=4a+4 | | 14-3a=-9a+7 | | 3(n+4)=2+4(n+1) | | 1/6y+4=-16 | | 2n+5=4n-15 | | x^+4x+3.5=0 | | 3/2(x-2)-5=-19 | | (y+3)^2=0 | | 4z+18=3z+2 | | 2+(-6)=x | | x(9-x)-2x(3-x)=3/7*7/3+x | | -6=-7+u | | y3=3y2-12y-18=0 | | 8×0=4n | | x/5-5/6=x/2+1/3 | | y/4+16=18 | | 13=7x-6 | | (2+5i)(2-5i)=0 | | 16-3(x+11)=x-3 | | 7-4z=2(2z+3) | | x/6+3=-3 | | |x-3|=6 | | -2-4=-5+c | | 4n-40=70(-2n+2) | | -7(x+5)-12=13+3 |